2019
DOI: 10.1111/edt.12534
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of the top 50 most cited articles published in the Dental Traumatology

Abstract: Background/Aims The impact of a scientific article in its respective field is reflected by its citation count. The purpose of this review was to conduct a citation analysis in order to identify and analyze the top 50 most cited articles published in Dental Traumatology since its inception in order to highlight the contribution of the journal to the field of Dental Traumatology. Methods Elsevier's Scopus was used to search and analyze the 50 most frequently cited scientific papers. After the screening process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 79 publications
(123 reference statements)
4
54
0
Order By: Relevance
“…A paper cited over 400 times has been considered as a “classic” (or highly cited) paper 17,18 . However, in some smaller fields, including Dental Traumatology, a paper with over 100 citations can be a classic 19,20 . Therefore, 25 papers (co)authored by Dr. Andreasen can be considered classics, as they have 100 or more citations in the WoS‐CC.…”
Section: Discussionmentioning
confidence: 99%
“…A paper cited over 400 times has been considered as a “classic” (or highly cited) paper 17,18 . However, in some smaller fields, including Dental Traumatology, a paper with over 100 citations can be a classic 19,20 . Therefore, 25 papers (co)authored by Dr. Andreasen can be considered classics, as they have 100 or more citations in the WoS‐CC.…”
Section: Discussionmentioning
confidence: 99%
“…The "Visualization of Similarities (VOS) viewer software" is widely to graphically illustrate the bibliometric parameters in mapping networks, which allow easy visualization of critical elements [2,[19][20][21]. The current study used VOS to represent a graphical mapping of keywords as identified bibliometric analysis to identify the focus of research in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…The top three most commonly reported types of document in the literature also indicate that original research was the focus amongst the dental fraternity worldwide, as opposed to reviews [ 24 ]. The relatively low numbers of systematic reviews, meta-analyses and randomized controlled trials might be of concern, as these provide the highest level of evidence according to the hierarchy of research evidence [ 25 ]. It is known however, that randomized controlled trials in dentistry are seen as very expensive, very slow, difficult to recruit suitable patients, and results are unhelpful when inconclusive [ 26 ].…”
Section: Discussionmentioning
confidence: 99%